Dissemination of instructional book on catfish cultivation: An effort for illiteracy eradication in minapolitan area - Ekowati, Dyah Worowirastri; Cholily, Yus Mochamad; Hakim, Riza Rahman; Artadana, Ida Bagus Made; Sumarsono, Puji; Lailiyah, Ummi Badriyatul (Journal of Community Service and Empowerment, 2020)
Probolinggo Regency has a low literacy rate (78.09%) which is below the average of the East Java Province (88.34%). This data is supported by the recapitulation results of the Directorate of Literacy and Equality Education in 2014 which states that the illiteracy rate in Probolinggo Regency is 64.163 people. Meanwhile, this regency is considered having a high potential in the field of fisheries through catfish farming, located in Sumberasih District. This article discusses the results of the dissemination of illiteracy eradication using instructional book of catfish cultivation. The empowerment method implemented was Empowerment and Development. The instruments used were interview, observation, document, questionnaire, and test. On trial phase, a mentoring was done to the learning community that was called WB. Prior to the mentoring session, pretest was implemented then posttest afterwards which were all done to the WB. Results show that there was an improvement on class average grade, previously it was 58,5 subsequently after the use of illiteracy eradication book, the average grade has improved to 79. The responses gathered from the WB towards the instructional book were very positive. Thus, instructional book of catfish cultivation can be used as a textbook in illiteracy tutorial in minapolitan area.